1997
DOI: 10.1093/emboj/16.10.2745
|View full text |Cite
|
Sign up to set email alerts
|

Bni1p and Bnr1p: downstream targets of the Rho family small G-proteins which interact with profilin and regulate actin cytoskeleton in Saccharomyces cerevisiae

Abstract: The RHO1 gene encodes a homologue of mammalian remains to be clarified whether these target proteins of RhoA small G-protein in the yeast Saccharomyces Rho are involved in the reorganization of actin cytocerevisiae. Rho1p is required for bud formation and is skeleton. Very recently, one of these proteins, Rho kinase, localized at a bud tip or a cytokinesis site. We have recently shown that Bni1p is a potential target of has been shown to inhibit the myosin phosphatase activity Rho1p. Bni1p shares the FH1 and F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
290
2
3

Year Published

1998
1998
2005
2005

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 296 publications
(301 citation statements)
references
References 67 publications
6
290
2
3
Order By: Relevance
“…However, strains lacking Bnr1p still transport vesicles from the mother to concentrate at the bud tip ( Figure 3A) and are able to grow with a normal morphology and rate (Imamura et al, 1997;Vallen et al, 2000), suggesting that the few Bni1p-dependent cables in the mother cell meet the transport requirements of the yeast cell under the conditions examined so far.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…However, strains lacking Bnr1p still transport vesicles from the mother to concentrate at the bud tip ( Figure 3A) and are able to grow with a normal morphology and rate (Imamura et al, 1997;Vallen et al, 2000), suggesting that the few Bni1p-dependent cables in the mother cell meet the transport requirements of the yeast cell under the conditions examined so far.…”
Section: Discussionmentioning
confidence: 88%
“…The FH1 region is a proline-rich stretch that recruits profilin, an actin-monomer binding protein essential for formin function in vivo , to participate in FH2-mediated nucleation in vitro (Sagot et al, 2002b;Kovar et al, 2003;Pring et al, 2003). Other regions present in Bni1p and Bnr1p are a regulatory NH 2 -terminal rho-GTPase-binding domain that subjects many formins to rho-dependent activation (Kohno et al, 1996;Evangelista et al, 1997;Imamura et al, 1997;Dong et al, 2003), and an FH3 motif that helps localize formins within the cell (Petersen et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bni1p is known to be implicated in cytokinesis and establishment of cell polarity (Jansen et al, 1996;Zahner et al, 1996). We have moreover found that Bni1p directly interacts with pro®lin, an actin monomer-binding protein, which accelerates the polymerization of actin (Imamura et al, 1997). It is likely that Rho1p regulates the reorganization of the actin cytoskeleton through the Bni1p-pro®lin system in the budding yeast.…”
Section: Introductionmentioning
confidence: 85%
“…Rho1p regulates the reorganization of the actin cytoskeleton at least through the Bni1p-pro®lin system in the budding yeast (Kohno et al, 1996;Imamura et al, 1997). We have examined a possible interaction of ABP140 with Rho1p, Bni1p, and pro®lin by use of the yeast two-hybrid system.…”
Section: Discussionmentioning
confidence: 99%